Identification of a novel proinsulin-associated SNP and demonstration that proinsulin is unlikely to be a causal factor in subclinical vascular remodelling using Mendelian randomisation. (November 2017) - Strawbridge, Rona J.; Silveira, Angela; Hoed, Marcel den; Gustafsson, Stefan; Luan, Jian'an; Rybin, Denis; Dupuis, Josée; Li-Gao, Ruifang; Kavousi, Maryam; Dehghan, Abbas; Haljas, Kadri; Lahti, Jari; et al.
Abstract: Background and aims: Increased proinsulin relative to insulin levels have been associated with subclinical atherosclerosis (measured by carotid intima-media thickness (cIMT)) and are predictive of future cardiovascular disease (CVD), independently of established risk factors. The mechanisms linking proinsulin to atherosclerosis and CVD are unclear. A genome-wide meta-analysis has identified nine loci associated with circulating proinsulin levels. Using proinsulin-associated SNPs, we set out to use a Mendelian randomisation approach to test the hypothesis that proinsulin plays a causal role in subclinical vascular remodelling. Methods: We studied the high CVD-risk IMPROVE cohort (n = 3345), which has detailed biochemical phenotyping and repeated, state-of-the-art, high-resolution carotid ultrasound examinations. Genotyping was performed using Illumina Cardio-Metabo and Immuno arrays, which include reported proinsulin-associated loci. Participants with type 2 diabetes (n = 904) were omitted from the analysis. Linear regression was used to identify proinsulin-associated genetic variants. Results: We identified a proinsulin locus on chromosome 15 (rs8029765) and replicated it in data from 20, 003 additional individuals. An 11-SNP score, including the previously identified and the chromosome 15 proinsulin-associated loci, was significantly and negatively associated with baseline IMTmean and IMTmax (the primary cIMT phenotypes) but not with progression measures. However, MR-Eggers refuted any significant effect of the proinsulin-associated 11-SNP score, and a non-pleiotropic SNP score of three variants (including rs8029765) demonstrated no effect on baseline or progression cIMT measures. Conclusions: We identified a novel proinsulin-associated locus and demonstrated that whilst proinsulin levels are associated with cIMT measures, proinsulin per se is unlikely to have a causative effect on cIMT. Highlights: Identification of a novel proinsulin-associated locus on chromosome 15. Lead chromosome 15 SNP rs8029765 influences expression of UNC45A in liver. Proinsulin effects on carotid intima-media thickness are segment-specific. Proinsulin-increasing SNP scores had limited effects on carotid intima-media thickness. Proinsulin is unlikely to have causal effects on intima-media thickness.